PN3b as an independent risk factor for poor prognosis and peritoneal recurrence in Borrmann type IV gastric cancer: A retrospective cohort study - Chen, Yiran; Chen, Yanyan; Wen, Liping; Tou, Laizhen; Wang, Haiyong; Teng, Lisong (Frontiers in Surgery, 2022)
Background: The clinicopathological features and surgical treatment strategies of Borrmann type IV gastric cancer (GC) remain controversial. Peritoneal metastasis is the most common recurrence pattern in patients with Borrmann type IV GC. Methods: Among 2026 gastric cancer between January 2009 and August 2019, 159 cases of Borrmann type IV GC were included in this study (7.8%). We retrospectively analyzed the clinicopathological characteristics and prognosis of these patients. Univariate and multivariate Cox proportional hazards were applied to identify independent prognostic factors. Predictors related to peritoneal metastasis of type IV GC were analyzed by multivariate Cox regression analysis. Results: Borrmann type IV gastric cancer was associated with more advanced clinicopathological features at diagnosis than the other Borrmann type GC. Of the 159 patients with Borrmann type IV GC, the median OS was 23 months. The number of patients with peritoneal metastasis was 43, accounted for 27.0% of all the patients and 87.8% of the patients with distant metastasis. Multivariate analyses revealed lymph node metastasis to be independent prognostic factor for survival in Borrmann type IV GC patients. pN3b and tumor size>50mm showed to be risk factors for peritoneal metastasis. Conclusions: Borrmann type IV GC is an important independent prognostic factor. pN3b is an independent prognostic factor and a predictor of peritoneal metastasis in patients with Borrmann type IV GC.